Union of South Africa . House of Assembly Debates - South Africa Parliament (Cape Town, 1947)
Debates of the House of Assembly of the Union of South Africa as reported in the Cape Times. Debates of the House of Assembly / Union of South Africa = Debatten van de Volksraad / Unie van Zuid-Afrika. South Africa Politics and government
108 v. South Africa Politics and government
Keywords: Union of South Africa; House of Assembly; 28 April 1947; 5 June 1947; Vol. 61; 1947; Index to subject; adjournment of House on definite matter of urgent public importance; Springbok Legion; squatters on Witwatersrand; Index to Speeches; Pieterse, Maj. P.W.A (Heilbron); Heilbron; Pocock, Mr P.V (Pretoria Sunnyside); Pretoria; Sunnyside; Wolmarans, Mr J.B (Losberg); Losberg; JC044721